CHARACTER ASSOCIATION AND PATH ANALYSIS FOR SEED YIELD AND LODGING TRAITS IN RICE (Oryza sativa L.) GENOTYPES - B. KEERTHIRAJ,; S. BIJU,; ANJU M. JOB, (The Bioscan, 2020)
The present study was carried out among 21 rice genotypes. Seeds for the study was collected from Rice Research Stations of Kerala Agricultural University (KAU). These genotypes were raised in RBD with two replications. The direct and indirect effects of seventeen traits including lodging and yield were estimated. The results from the correlation studies showed that grain yield plant -1 recorded positive correlation at high significance at both genotypic and phenotypic levels with number of panicles plant -1 (rp=0.806, rg=0.822) followed by number of tillers plant -1 (rp=0.753, rg=0.773), test weight and silicon content. Lodging% exhibited highly significant and positive correlation at both phenotypic and genotypic levels with days to 50% flowering, plant height, flag leaf length, internodal length, culm diameter, days to maturity and panicle length. Path analysis revealed that panicles plant -1 (1.064) had very high positive direct effect on yield followed by flag leaf length (0.824), seeds panicle-1 (0.785), test weight (0.607) and panicle weight. Among these traits, number of panicles plant -1 and test weight possessed both positive association and high direct effects. Meanwhile, plant height, internodal length and culm diameter possessed negative effects. Hence, selection for these traits could bring improvement in yield and yield components along with lodging resistance.